Impact of Integrated Sericultural Technologies on Cocoon Productivity at Farmer Level - Dayananda; P. Kumaresan (Journal of Agricultural Extension Management, 2025)
A study was conducted during 2005-06 to 2006-07 in Anekal division of Bangalore district, Karnataka to know the impact of group demonstration of integrated sericultural technologies (1ST) on knowledge and adoption of sericultural technologies by farmers. Two villages were identified and 20 farmers each in selected villages were randomly selected whose benchmark mulberry yield was less than 40.00 MT/ha/year and cocoon yield was less than 40 kg/ 100 disease free laying (dfls) before initiating the group demonstration. At the beginning of the demonstration of /ST, a baseline survey of selected farmers with respect to knowledge and adoption level of different sericultural technologies and their sericulture productivity level was carried out. The demonstration of /ST covering 20 sericultural technologies was conducted in the field among the selected farmers who were guided in their sericulture activities for a period of two years. After two years, the impact of demonstration on knowledge and adoption level of sericultural technologies and improvement in mulberry and cocoon productivity levels were assessed among the selected farmers. The results reveal an improvement in knowledge level, adoption level among the selected farmers besides an improvement in the leaf yield and cocoon yield over the bench mark.